INTERCULTURAL DYNAMICS AND GROUP IDENTITY AMONG CHILDREN IN DIVERSE EDUCATIONAL CONTEXTS - wijaya wijaya; Jaden Tan; Rachel Chan (Yayasan Adra Karima Hubbi, 2026)
Increasing cultural diversity in contemporary educational settings has transformed schools into important social spaces where children encounter, interpret, and negotiate cultural differences. These interactions play a crucial role in the early formation of group identity, belonging, and social relations. This study aims to examine intercultural dynamics and the processes of group identity formation among children in diverse educational contexts, with particular attention to everyday peer interactions and classroom practices. The research employed a qualitative-dominant mixed-methods design involving classroom observations, semi-structured interviews with children and teachers, and sociometric mapping in culturally diverse primary schools. The findings reveal that children frequently form peer groups based on cultural and linguistic familiarity, while intercultural interaction increases primarily in structured learning situations supported by teacher mediation. Differences in perceived group belonging between majority and minority cultural groups indicate uneven experiences of inclusion within the same educational environments. The study concludes that cultural diversity alone does not automatically foster inclusive group identity among children. Intentional pedagogical strategies, cooperative learning structures, and supportive school cultures are essential in promoting meaningful intercultural engagement and equitable social participation. These findings underscore the central role of schools in shaping children’s early experiences of diversity and contribute to a deeper understanding of how inclusive group identities can be cultivated in multicultural educational settings.